‘Wish you were here’: Managers’ experiences of hybrid work in higher education - Helena Tinnerholm Ljungberg; Martina Wallberg; Emmanuel Aboagye; Gunnar Bergström; Christina Björklund; Lydia Kwak; Susanna Toivanen; Irene Jensen (PLoS ONE, 2025)
The prevalence of telework increased dramatically during the COVID-19 pandemic, and today it is not uncommon to refer to hybrid work as “the new normal” in work life. Leadership plays a pivotal role in hybrid work transitions, underscoring the need for research on post-pandemic managerial practices. This qualitative interview study with 15 professional service managers at a Swedish medical university, working in either central administration or a research department, provides a nuanced understanding of the experiences of implementing hybrid work in a higher education setting. The qualitative content analysis resulted in three main themes and six sub-themes: New ways of organising work (sub-themes: Hybrid work brings new opportunities and needs, and Hybrid work as an ongoing process of change); Changes for employees (sub-themes: Social interaction and sense of community, and Increased work-life balance); and Changes in leadership (sub-themes: Communication with employees and New expectations on managers). The findings of this study provide a more fine-grained understanding of how managers experienced both challenges and opportunities in implementing and managing hybrid working arrangements. Challenges included managing employee expectations and relations, while opportunities included potential improvements in work-life balance. A key conclusion of this study is that managers in hybrid work environments adjust their leadership, especially when communicating and managing relationships within teams and across the organization. Despite the identified challenges and despite managers’ wish to see their employees in person and on site, the interviewed managers are generally optimistic about hybrid work and see it as the future. To address the identified challenges, managers may benefit from networking and exchanging information with other managers in similar situations, as well as support from their organisation.